The contribution of product strategy towards readers' acceptance of the New Straits Times / Muhamad Azhar Parid Azmi - Azmi, Muhamad Azhar Parid (Faculty of Business and Management, 2007)
The purpose of this research is to study the contribution of product strategy towards readers' acceptance of the New Straits Times. The New Straits Times has a lower readership among NTSP group newspaper. So to increase the readership of the newspaper, product strategy will be the main factors in the contributing toward readers' acceptance of the newspaper. This study also wants to analyze the relationships between design and consumer acceptance, to identify the relationships between quality and consumer acceptance and to understand the relationships between price and consumer acceptance. Moreover, this study will examine the significance relationship between design and consumer acceptance, the significance relationship between quality and consumer acceptance, and significance relationship between price and consumer acceptance. The survey is conducted at area Bangsar, Damansara, and Klang Lama. The sample size for this study is 50 customers who are also have experience in using the New Straits Times. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that include the statements regarding factors influencing acceptance toward the New Straits Times. Once the necessary data has been collected, the data will be analyzed and summarized in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 15.0 has been used to summarize the data. The results are in the form of reliability testing, frequency and correlation. Based on this research, the findings showed that there are significance relationships between design and quality towards consumer acceptance. For the meantime, there is also a significance relationship between price and consumer acceptance. The researcher is also able to give some recommendations and suggestion on the best product strategy towards consumer acceptance after the analysis, findings and interpretation.